Analysis of Business Process Improvement Using the Business Process Improvement (BPI) Method in the Catfish Fisheries Sector in Batuliman Indah Village, South Lampung Regency - Akmal Sahuda; M. Oktavianur; Niki Agus Santoso (Eastasouth Institute, 2026)
This study examines business process improvement in catfish farming enterprises using the Business Process Improvement (BPI) method in Batuliman Indah Village, South Lampung Regency. Catfish farming plays an important role in supporting local livelihoods and meeting increasing market demand; however, many small-scale producers continue to face operational and managerial challenges that reduce efficiency and business sustainability. Data were collected through field observations, semi-structured interviews with 9 respondents consisting of catfish farmers and related stakeholders, and document analysis. The study begins by mapping the existing business processes (As-Is) across key production stages, including pond preparation, seed stocking, feeding, maintenance, harvesting, and marketing. The BPI framework is then applied to identify value-added and non-value-added activities, analyze root causes of process inefficiencies, and design proposed improved processes (To-Be). The findings reveal that major problems in the current business processes include the absence of standardized operating procedures and systematic record-keeping, inefficient feed utilization, unstable water quality management, relatively high fish mortality rates, and strong dependence on intermediaries in the marketing process. Based on the BPI analysis, proposed process improvements focus on workflow simplification, standardization of operational procedures, enhancement of monitoring and documentation systems, and reduction of non-value-added activities. The study concludes that an integrated application of Business Process Improvement can significantly improve operational efficiency, managerial control, and consistency of catfish farming activities, thereby supporting more sustainable and competitive small-scale aquaculture enterprises. The results of this research are expected to provide practical insights for farmers, extension agencies, and policymakers in improving business process management within the fisheries sector.